Hubungan Sosial Ekonomi dan Riwayat ASI Eksklusif dengan Kejadian Stunting pada Balita 24-59 Bulan di Wilayah Kerja Puskesmas Pantoloan - Siti Nuraisyah Lengkong; Aulia Rakhman; Nur Afia Amin; Abdul Fandir (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Stunting is a growth disorder in children caused by chronic nutritional problems during the first 1,000 days of life, characterized by a height shorter than the age standard. This condition is influenced by socioeconomic factors and exclusive breastfeeding history, which is defined as the provision of breast milk alone without additional food for the first six months since birth. This study aims to identify the relationship between socioeconomics and exclusive breastfeeding history with the incidence of stunting in toddlers 24-59 months in the Pantoloan Health Center working area. This research method used an analytic survey with a cross-sectional approach. The population consisted of all toddlers aged 24-59 months, namely 1,249 toddlers, while the sample amounted to 102 toddlers. The sampling technique used purposive sampling. Data analysis using univariate and bivariate tests. The results of bivariate analysis using the chi-square test showed that there was a relationship between mother's work (p=0.021) with the incidence of stunting, there was no relationship between father's education (p=236) with the incidence of stunting, there was a relationship between mother's education (p=0.097) with the incidence of stunting. there was a relationship between parental income (p=0.013), and there was a relationship between exclusive breastfeeding history (p=0.001). It is recommended for the community, especially parents and prospective parents, to prevent stunting early on. Stunting prevention is recommended to commence during pregnancy through proper planning and adequate nutritional fulfillment; meanwhile, future researchers are encouraged to utilize longitudinal designs and incorporate environmental variables to obtain a more comprehensive understanding of stunting determinants